The Influence of Cognitive and Environmental Stimulation on Children's Language Acquisition - M, Asia (Journal La Edusci, 2025)
Early childhood language development relies heavily on cognitive processes together with environmental quality of stimulation. This quantitative investigation determines the measures to which both cognitive engagement and environmental elements contribute towards children's language growth. A standard survey and official language testing instruments gathered information from three hundred children between ages 3 and 6 from distinct economic groups. The statistical analysis using multiple regression demonstrates that cognitive stimulation (β = 0.55, p < 0.001) as well as environmental stimulation (β = 0.41, p < 0.001) serve as significant predictors of language acquisition with an explanation of 56% (R² = 0.56). The study confirmed that socio-economic status affects language development (β = 0.29, p < 0.001) yet both cognitive and environmental stimulation variables mediated the relationship between these factors thereby reducing the impact of socio-economic factors on language development. The research helps expand current knowledge through quantitative evidence supporting cognitive and environmental factors while analyzing the combined learning environments of homes and schools and overcoming rigid views about SES's effect on language development. The analysis demonstrates why educational approaches that include student interactions matter together with early literacy initiatives and controlled linguistic and education programs during early childhood. Researchers emphasize the necessity of government programs that actively improve both intellectual and environmental stimulation in child education facilities. The study yields valuable findings yet future research must use longitudinal studies to track longer-term consequences between these factors and diverse dimensions of language development.